Personafying academic librarians’ social media presence - Zohoorian-Fooladi, Niusha; A., Abrizah; Zohoorian-Fooladi, Niusha; Abrizah, A. (Malaysian Journal of Library and Information Science, 2017)
Zohoorian-Fooladi, N., & Abrizah, A. (2014). Personifying academic librarians’ social media presence. Malaysian Journal of Library and Information Science, Vol.19, no. 3: 13-26. Persona is an approach for system designer to group users based on their common characteristics and personafying refers to the configuration of a concept or practice in the form of a persona. The objective of the study is to explain how persona method can be helpful to illustrate academic librarians’ social media presence with respect to their awareness, current practices and readiness. The study uses qualitative research design in a form of case study to understand how librarians know, use and implement social media in the delivery of library services. Data was gathered through interviews with 26 academic librarians and three focus groups sessions of librarians from three research intensive universities in Malaysia. Findings show that librarians illustrate different behaviour to show how their social media awareness, practices and readiness determine the personas into which they were grouped: Skaters, Sliders, Shufflers and Starters. This stream of research on the personas method will provide library managers with results that can be useful to show librarian’ behaviour in using social media, and how library management can use it to design library services to reach out to wider audiences. Moreover, library managers can direct subordinate librarians to become more active and participatory in creating their social media presence. It is hoped that the method presented in this paper would be easy to perceive and be translatable into practice.